Areca Nut Chewing: Initiation, Addiction, and Harmful Effects Emphasizing the Barriers and Importance of Cessation. (3rd June 2021) - Athukorala, I. A.; Tilakaratne, W. M.; Jayasinghe, R. D.
Abstract : Areca nut is a highly addictive substance with carcinogenic properties and causes many harmful effects to the human body. Alkaloids are the major chemicals found in areca nut, and their mechanism of action has been studied for several years. About 600 million people around the world use areca nut, and its usage is higher in Asian countries. Areca nut chewers get used to the habit mainly due to social influence, stress, or lack of awareness. Some studies have reported a dependence syndrome related to areca nut chewing. Even though there are many ongoing research studies regarding tobacco addiction, less concern has been given to the areca nut addiction. There are only few studies related to areca nut cessation, and even those few cessation programs are mainly designed using tobacco cessation methodology. Sociocultural influence, behavioral factors, and accessibility are the main barriers to cessation. Behavior changing interventions proved to be more effective in areca nut cessation, but recently studies on pharmacological therapies are also emerging.